Differential Impact of Changes in Adiposity Distribution on Insulin Resistance and Adiponectin Variations Over 4 Years in Normal Weight Young Adults - Lacerte, G.; Langlois, M.-F.; Doyon, M.; Brown, C.; Carpentier, A. C.; Hivert, M.-F. (Hormone and Metabolic Research, 2014)
The aim of the study was to evaluate the influence of weight gain and changes in adiposity distribution on insulin resistance and circulating adiponectin variations over 4 years in free-living normal weight young adults. In this prospective observational cohort (n=42 women, 18 men), anthropometric measurements and blood samples were collected in the fasting state at baseline and at 4 years. Insulin resistance was estimated using the homeostatic model assessment (HOMA-IR). Circulating adiponectin levels were determined by radioimmunoassay. To investigate increase in adiposity more specifically, subsidiary analyses were performed in a subgroup of individuals (n=31) who gained adiposity over the course of the 4-year follow-up (defined as gain >1% in percent body fat). Regression analyses were performed to adjust for sex, age, parental education, lifestyle, and fitness levels. At baseline, the participants were young adults (age=20.0 years old) in the normal weight range [body mass index (BMI)=22.7 kg/m2 (IQR=21.1–24.4)]. Median change in body fat percentage was +1.4% (IQR=−0.3–3.4; p=0.01) and in waist circumference was +1.2 cm (IQR=−2.6–5.3; p=0.05). In the subgroup of individuals who gained more than 1% body fat, increase in HOMA-IR was associated with an increase in BMI (r=0.44; p=0.01; p<0.01 in fully adjusted model), while decrease in adiponectin levels was associated with an increase in waist circumference (r=−0.38; p=0.03) but this was no longer significant after adjustment for sex and other potential confounders (p=0.14). In a population of young adults, small variations in adiposity within the normal weight range were associated with increase in insulin resistance.
Keywords: weight gain; waist circumference; percent body fat; adiponectin; insulin resistance; young adults